Effect of sex and combat employment on musculoskeletal injuries and medical downgrading in trained military personnel: an observational cohort study. Issue 1 (19th January 2023) - Wardle, Sophie L; O'Leary, T J; Jackson, S; Greeves, J P
Abstract : Introduction: Following the opening of all combat roles to women across the UK Armed Forces, there is a requirement to understand the risk of injury to these female personnel. Women injure at a higher rate than men during basic military training, but fewer data are published from individuals who have passed military training. Methods: A bespoke survey was designed to investigate differences in injury prevalence and medical downgrading between sexes and career employment groups (ie, job roles) in the UK Armed Forces. Results: Questionnaire data were evaluated from 847 service personnel (87% men) employed in combat roles (Royal Marines, Infantry, Royal Armoured Corps, Royal Air Force Regiment (all men)) and non-combat roles (Royal Regiment of Artillery, Corps of Royal Engineers, Royal Logistic Corps and Combat Service Support Corps who were attached to one of the participating units (men and women)). Women reported more total (OR 1.64 (95% CI: 1.03 to 2.59), p=0.035), lower limb (OR 1.92 (95% CI: 1.23 to 2.98), p=0.004) and hip (OR 2.99 (95% CI: 1.59 to 5.62), p<0.001) musculoskeletal injuries in the previous 12 months than men, but there were no sex differences in the prevalence of current or career medical downgrading due to musculoskeletal injury (both p>0.05). There were no differences in 12-month musculoskeletal injury prevalence between men in combat roles and men in non-combat roles (all p>0.05), but men in non-combat roles were more likely to be currently medically downgraded (OR 1.88 (95% CI: 1.27 to 2.78), p=0.001) and medically downgraded during their career (OR 1.49 (95% CI: 1.11 to 2.00), p=0.008) due to musculoskeletal injury than men in combat roles. More time in service and quicker 1.5-mile run times were associated with increased prevalence of total musculoskeletal injuries, and female sex was a predictor of hip injury. Conclusions: Although women are at greater risk of injury than men, we have no evidence that combat employment is more injurious than non-combat employment. The prevention of hip injuries should form a specific focus of mitigation efforts for women.